Bulgaria : Staff Report for the 2000 Article IV Consultation and Fifth Review Under the Extended Arrangement. (IMF Staff Country Reports; Country Report, 2001)
Bulgaria's currency board arrangement continues to have broad political and public support and shows no signs of strain, as interest rates are low and stable, fiscal reserves ample, and banks liquid. A structural reform agenda has also been implemented. The authorities have improved banking supervision, started the overhaul of the pension and health care systems, and liberalized trade and prices. Executive Directors stressed the need to strengthen the bank supervision and corporate governance to reduce the perceived risks of lending to the private sector.